2014
DOI: 10.5194/os-10-881-2014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extreme regional sea surface height due to an abrupt weakening of the Atlantic meridional overturning circulation

Abstract: Abstract.As an extreme scenario of dynamical sea level changes, regional sea surface height (SSH) changes that occur in the North Atlantic due to an abrupt weakening of the Atlantic meridional overturning circulation (AMOC) are simulated. Two versions of the same ocean-only model are used to study the effect of ocean model resolution on these SSH changes: a high-resolution (HR) strongly eddying version and a low-resolution (LR) version in which the effect of eddies is parameterised. The weakening of the AMOC i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
(67 reference statements)
1
20
0
Order By: Relevance
“…The freshwater input (G S = 0.5 Sv) has a strong impact on the three-dimensional ocean circulation (Brunnabend et al, 2014). The Gulf Stream and North Atlantic current shift to the east (Fig.…”
Section: Response To Freshwater Anomaliesmentioning
confidence: 99%
“…The freshwater input (G S = 0.5 Sv) has a strong impact on the three-dimensional ocean circulation (Brunnabend et al, 2014). The Gulf Stream and North Atlantic current shift to the east (Fig.…”
Section: Response To Freshwater Anomaliesmentioning
confidence: 99%
“…This current is climatically important (Jackson et al, 2015) with model simulations predicting a decrease in AMOC in response to increasing greenhouse gases (Solomon et al, 2007;Liu et al, 2015). Models also suggest the potential for significant mean sea level (MSL) changes across the western North Atlantic in response to AMOC dynamics (Brunnabend et al, 2014). In terms of mass transport Thomas et al (2012) found that a weakening AMOC would be manifested as a reduction in southward deep water transport balanced by a decline in the northward upper ocean western boundary current.…”
Section: Introductionmentioning
confidence: 99%
“…[], and Brunnabend et al . []. Modeled sea level change that is induced by the land ice mass loss can be separated into its mass and steric contribution.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of the additional freshwater inflow around Greenland influenced the amplitude of the signal. However, it had only a small influence on the structure of the pattern, which may change when the additional mass loss would become high enough to alter the ocean circulation pattern [ Brunnabend et al ., ].…”
Section: Introductionmentioning
confidence: 99%